Integrasi Etnosains Pada Pembelajaran IPA: Studi Lapangan pada Batik Tulis Giriloyo dan Candi Prambanan - Thufail Mujaddid Al-Qoyyim; Aprilia Maharani; Fitratunisyah Fitratunisyah; Eka Muliati; Sulis Rahmatia; Wardi Kurniawan; Satutik Rahaya; Muh, Makhrus (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study explores the integration of ethnoscience and ethnopedagogy into science learning by examining two cultural sites in Yogyakarta: Batik Tulis Giriloyo and the Prambanan Temple. Using qualitative descriptive methods, the research identifies scientific phenomena embedded in traditional batik production,such as chemical reactions in natural dyes, heat transfer in wax processing, and biological aspects of plant-based pigments,as well as physical, chemical, and ecological processes observable in the architecture and environment of Prambanan. These findings are then connected to science learning competencies at the junior and senior high school levels, demonstrating the relevance of culturally grounded phenomena to concepts such as states of matter, diffusion, oxidation, biodegradation, structural stability, and ecosystem dynamics. The study proposes a culturally embedded IPA learning model consisting of five stages: cultural orientation, artifact-based scientific exploration, simple experiments, value reflection, and the strengthening of character and scientific literacy. The integration of ethnoscience enriches conceptual understanding, while ethnopedagogical values, such as patience, accuracy, harmony, and environmental awareness, support character development. This approach aligns with the principles of the Merdeka Curriculum, emphasizing authentic, contextual, and culturally responsive science learning.